PHYSIOLOGICAL EFFECTS OF REHABILITATION ON THE BODY (Web of Teachers: Inderscience Research, 2026)
Rehabilitation remains a cornerstone in modern medicine in enhancing health, restoring lost functions, and supporting individuals through the recovery process after disease or injury. Diving into the physiological implications provides a deeper understanding of why and how rehabilitation can change bodily processes, both in the short and long term. The role of rehabilitation encompasses a wide spectrum, from physical therapy to occupational and speech therapy, each exerting distinct, yet interconnected, influences on the human body.